"Clearing a Path for Television News": The First Extended Newscast at Sacramento's KCRA. Issue 4 (1st January 2017) - Liseblad, Madeleine
Abstract : The advent of extended television news was a turning point for television, a medium originally devoted to entertainment. Starting in the 1970s, scholars associated extended news with the first half-hour network newscasts. However, later scholarship has shown extended news was driven by local television stations, not the networks. At least nine local stations introduced a forty-five minute evening newscast well before the network expansion. This article examines in depth the previously virtually ignored first known extended newscast in the nation¯KCRA's Channel 3 Reports¯ launched in Sacramento, California, on February 20, 1961, at 6 p.m. Channel 3 Reports provided viewers with a one-hour newscast, with forty-five minutes of locally produced content, along with fifteen minutes of delayed electronic feeds containing network news. KCRA's newscast began two and a half years before the network news expansion. Prominent local newscasts, including KNXT's The Big News in Los Angeles followed in KCRA's footsteps.